(untitled) (Research, Society and Development, 2022)
The rapid spread of COVID-19 worldwide, resulting from the high viral transmissibility of Sars-CoV-2, associated with the lack of specific and effective vaccines and antivirals for the prevention and treatment of the disease, made non-pharmacological interventions the most efficient options for the mitigation and control of the pandemic. This study investigated preventive measures adopted and the profile of self-medication, in COVID-19, in residents of a vertical residential condominium in the city of Curitiba, Paraná. It was a cross-sectional study with convenience sampling technique. Data collection occurred via online questionnaire, previously validated. The results show that preventive measures were used by the research participants, although 20% of the residents who were positive or in contact with positive cases for COVID-19 did not respect the rule of social isolation, contributing to the increase in the number of infected. Self-medication was observed in 66% of the residents and ivermectin was the most commonly used drug as prevention and treatment of the pandemic. Irrational use of medication and failure to comply with social isolation, even when possible, are difficulties that slow down the fight against Sars-CoV-2.